1992
DOI: 10.1210/en.130.6.3223
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone inhibits the estrogen-induced expression of c-fos messenger ribonucleic acid in the uterus

Abstract: Estradiol produces a large increase in the uterine level of c-fos mRNA, which is maximum in 3 h. The administration of progesterone antagonizes this estrogen-induced increase in protooncogene transcript levels in both the rat and mouse. The inhibitory effect of progesterone is observed within 1 h after hormone treatment and persists for 9-18 h. In the rat, this effect can be observed at a dose of 0.25 mg progesterone and is maximum at a dose of 2.5 mg. A similar inhibition of fos mRNA levels after estrogen adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 0 publications
1
29
0
2
Order By: Relevance
“…For example, downregulation of the chicken c-jun gene in the oviduct by progesterone occurs at the level of transcription within 15 min and requires only 30 min to decrease the levels of mRNA (31). Interestingly, in nonpregnant rats, progesterone administration blocks the estradiol-induced increase in c-fos mRNA within 1 h, consistent with a mechanism in which progesterone inhibits transcriptional activation by the estrogen receptor, but it has no effect on the TPA-induced increase in c-fos mRNA after 3 h, although longer time points were not investigated (12). These results indicate the diverse signaling pathways through which c-fos induction can occur in myometrial cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, downregulation of the chicken c-jun gene in the oviduct by progesterone occurs at the level of transcription within 15 min and requires only 30 min to decrease the levels of mRNA (31). Interestingly, in nonpregnant rats, progesterone administration blocks the estradiol-induced increase in c-fos mRNA within 1 h, consistent with a mechanism in which progesterone inhibits transcriptional activation by the estrogen receptor, but it has no effect on the TPA-induced increase in c-fos mRNA after 3 h, although longer time points were not investigated (12). These results indicate the diverse signaling pathways through which c-fos induction can occur in myometrial cells.…”
Section: Discussionmentioning
confidence: 94%
“…In nonpregnant rats, it has been shown that treatment with progesterone prevents the induction of c-fos mRNA by estrogen; however, the mechanisms that mediate this inhibition have not been characterized (12). These complex in vivo interactions of endocrine, paracrine, and mechanical signals at term in the myometrium complicate the analysis of the role of these signals in AP-1 gene expression.…”
mentioning
confidence: 99%
“…Moreover, there are only a few reports concerning androgen-dependent potentiation of neuronal c-Fos expression [13]. For example, testosterone augments odor-induced neuronal c-Fos throughout the vomeronasal projection [14], but it does not block the estradiol-induced increase in c-fos mRNA in the uterus [15].…”
mentioning
confidence: 99%
“…In many cases, progestins suppress the stimulatory effects of estrogens in target cells. For example, estrogen increases the expression of both c-fos and PR mRNA in uterine cells, and progestins block these effects (14,16,21). Although a number of endpoints for progestin antagonism of estrogen action have been examined, the molecular mechanisms underlying the antagonism have not been elucidated.…”
mentioning
confidence: 99%